2012
DOI: 10.1186/1472-6874-12-39
|View full text |Cite
|
Sign up to set email alerts
|

The health of women in the US fire service

Abstract: BackgroundDespite statements from national fire service organizations, including the International Association of Fire Fighters (IAFF) and the International Association of Fire Chiefs (IAFC), promoting a diverse work force related to gender within the fire service, rates of women firefighters remain very low. Thus, research into why this extensive gender disparity continues is a high priority. Recent years have seen a number of large scale studies on firefighter health and health risk behaviors however, none h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 31 publications
(44 reference statements)
1
51
0
3
Order By: Relevance
“…In the general Australian population, the smoking rates were 13.1% for women and 18.2% for men 16. A US firefighters’ study also showed that female career full-time firefighters smoked more than women in the general population,17 and found a non-statistically significant elevated rate of lung cancer among women who had turned out to incidents but the rate was not elevated among those who had not turned out. No other studies of cancer among female volunteer firefighters have been identified in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…In the general Australian population, the smoking rates were 13.1% for women and 18.2% for men 16. A US firefighters’ study also showed that female career full-time firefighters smoked more than women in the general population,17 and found a non-statistically significant elevated rate of lung cancer among women who had turned out to incidents but the rate was not elevated among those who had not turned out. No other studies of cancer among female volunteer firefighters have been identified in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, firefighters who screened positive for problem drinking were significantly less likely to say they would recommend a career in the fire service to other women. Given the difficulties recruiting women into this occupation, creating a more inclusive Fire Service will likely require interventions targeting factors associated with excessive drinking (Jahnke, Poston, Haddock, et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…These techniques are widely accepted for recruitment among underserved, hidden populations (Sadler, Lee, Lim, & Fullerton, 2010). The primary outlets used for recruitment included: 1) contacting participants from previous studies (Jahnke, Poston, Haddock, et al, 2012); 2) through iWomen membership, the only national organization representing women in the fire service; 3) email distribution through the International Association of Fire Fighters (IAFF), the national labor union for firefighters; 4) through the Center for Fire, Rescue & EMS Health Research’s email distribution list to previously collaborating fire service personnel; and 5) a posting on the “Secret List,” which is a popular email listserv in the fire service that is distributed to thousands of firefighters worldwide. Secondary recruitment included requesting any women completing the survey to share the solicitation with their women colleagues.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations